A Cluster Set Protocol in the Half Squat Exercise Reduces Mechanical Fatigue and Lactate Concentrations in Comparison with a Traditional Set Configuration - Daniel Varela-Olalla; Alejandro Romero-Caballero; Juan Del Campo-Vecino; Carlos Balsalobre-Fernández (MDPI AG, 2020)
Splitting sets into clusters has been shown to maintain performance during resistance training. This study compared the acute fatigue produced by a traditional (TSC) versus a cluster (CSC) set configuration in the smith machine half squat exercise. Fifteen males performed a single bout of TSC and CSC separated by 72-96 h. In the TSC, participants performed as many repetitions as possible until reaching a 20% drop in barbell velocity (MPV), while in the CSC, they performed the same number of repetitions with 15 seconds inter-repetition rest. Effects of both protocols in MPV, countermovement jump height (CMJ), and blood lactate (BLa) were measured. Significant differences between protocols were found for MPV of the last repetition (0.4 vs 0.5 m/s TSC and CSC) and BLa (6.8 mmol/L vs 3.2 mmol/L TSC and CSC). Significant drop of velocity from the first to the last repetition of the set (19.9%), decrease in CMJ height (35.4 vs 32.6 cm), and increase in BLa (2.1 vs 6.8 mmol/L) pre-post-exercise was observed just for the TSC protocol. The results of the present study showed that CSC reduces the lactate response and mechanical fatigue produced by a single set on the half squat exercise in comparison with TSC.